Uzdevumi sākumskolas skolēnu angļu valodas izrunas pilnveidei - Mašinska, Krista (Latvijas Universitāte, 2020)
Izruna ir nozīmīga angļu valodas apguves daļa. Izrunas prasmes ietekmē spēju radīt skaņas, saprast valodu un uztvert teiktā nozīmi, kas ir būtiski faktori, lai veidotu veiksmīgu komunikāciju. Šī iemesla dēļ sākumskolas angļu valodas stundās vairāk uzmanības būtu jāvelta izrunas uzlabošanas vingrinājumiem. Izvēloties vingrinājumus, nepieciešams ņemt vērā izrunas apguves īpatnības jaunākā skolas vecuma skolēniem. Lai noteiktu metožu un vingrinājumu efektivitāti izrunas prasmju uzlabošanai sākumskolā, tika pielietotas divas mācību metodes, audiolingvālā mācību metode un tiešā metode, Tukuma 2. vidusskolas 4. klases skolēnu angļu valodas stundās. Noslēguma diagnosticējošais tests apstiprināja, ka abas izvēlētās mācību metodes palīdzēja uzlabot sākumskolas skolēnu angļu valodas izrunas prasmes.

Pronunciation is an essential part of the English language learning as it affects intelligibility, comprehensibility and interpretability, which are crucial aspects for successful communication. For this reason, more attention should be dedicated to the pronunciation improvement exercises during English lessons in primary school. Peculiarities of English pronunciation acquisition for young learners should be taken into consideration while selecting the exercises for pronunciation improvement. To determine the effectivity of methods and exercises for pronunciation skill improvement in primary school, two teaching methods, the Audio-lingual and the Direct Method, were implemented in English lessons of Form 4 in Tukums Secondary School No. 2. The results of the final diagnostic test proved that both methods had an impact on the improvement of primary school learners’ English pronunciation skills.
Activities to Improve Students' English Pronunciation Skills in Primary School
Keywords: Pedagoģija; young learners; pronunciation; digraphs; Audio-lingual teaching method; Direct Method